Monetary policy, cash flow and corporate investment: Empirical evidence from Vietnam - Linh My Tran; Chi Hong Mai; Phuoc Huu Le; Chi Linh Vu Bui; Linh Viet Phuong Nguyen; Toan Luu Duc Huynh (Journal of Risk and Financial Management, 2019)
This paper examines the relationships between macroscopic determinants (typically, monetary policies) and microscopic factors (mainly, cash flows and other controlling variables) on corporate investment. By employing system-GMM estimation for the 250 Vietnamese non-financial firms, the authors find that the expansionary monetary policy not only encourages the borrowing activities but also results in more corporate investment activities over the period from 2006 to 2016. Noticeably, the internal cash flow is also significant factor, which enhances the activities of corporate investment. Finally, there are differences between internal cash flow effects on corporate investments between two groups, divided by three theoretical criteria. To recapitulate, our implications highlight the importance of monetary policy stability for sustainable growth in corporate investment in Vietnam.
Keywords: E52; M21; D92; 330; monetary policy; cash flow; investment; GMM